Theoretical study of the open-flavored tetraquark $$T_{c\bar{s}}(2900)$$ T c s ¯ ( 2900 ) in the process $$Λ _b→ K^0D^0Λ $$ Λ b → K 0 D 0 Λ - Wen-Tao Lyu; Yun-He Lyu; Man-Yu Duan; Guan-Ying Wang; Dian-Yong Chen; En Wang (European Physical Journal C: Particles and Fields)
Abstract Recently, the LHCb Collaboration has measured the processes $$B^+→ D^-D_s^+π ^+$$ B + → D - D s + π + and $$B^+→ \bar{D}^0D_s^+π ^+$$ B + → D ¯ 0 D s + π + , where the $$D_s^+π ^-$$ D s + π - and $$D_s^+π ^+$$ D s + π + invariant mass distributions show the significant signals of two new open-flavored tetraquark states $$T_{c\bar{s}}(2900)^0$$ T c s ¯ ( 2900 ) 0 and $$T_{c\bar{s}}(2900)^{++}$$ T c s ¯ ( 2900 ) + + , as the two of the isospin triplet. In this work, we have investigated the process $$Λ _b→ K^0D^0Λ $$ Λ b → K 0 D 0 Λ by taking into account the tetraquark state $$T_{c\bar{s}}(2900)^0$$ T c s ¯ ( 2900 ) 0 and the intermediate nucleon resonance $$N^*(1535)$$ N ∗ ( 1535 ) , which could be dynamically generated by the interactions of the $$D^*K^*/D^*_sρ $$ D ∗ K ∗ / D s ∗ ρ and the pseudoscalar meson-octet baryon, respectively. Our results show that a clear peak of the open-flavored tetraquark $$T_{c\bar{s}}(2900)$$ T c s ¯ ( 2900 ) may appear in the $$K^0D^0$$ K 0 D 0 invariant mass distribution of the process $$Λ _b→ K^0D^0Λ $$ Λ b → K 0 D 0 Λ , which could be tested by future experiments.